Pelatihan Pemanfaatan Artificial Intelligence (AI) Berbasis ChatGPT untuk Meningkatkan Kompetensi Digital Guru dan Tenaga Kependidikan di SMK Bina Bangsa Mandiri Bogor - V. H. Valentino; Rudi Prasetya; Dewi Leyla Rahmah; Rudi Hermawan (Jurnal Kemitraan Masyarakat, 2026)
The rapid development of Artificial Intelligence (AI) technology has significantly transformed various sectors, including education. However, many teachers and educational staff still have limited understanding and skills in utilizing AI-based tools to support teaching, learning, and administrative activities. This community service program aimed to improve the digital competencies of teachers and educational staff at SMK Bina Bangsa Mandiri Bogor through training on the use of ChatGPT-based Artificial Intelligence. The program was conducted using a participatory approach consisting of needs assessment, training preparation, implementation, mentoring, and evaluation stages. The training materials covered the fundamentals of Artificial Intelligence, the introduction of ChatGPT, prompt engineering techniques, AI-assisted learning material development, educational content generation, and administrative document preparation. The participants were actively involved through lectures, demonstrations, hands-on practice, discussions, and mentoring sessions. The results indicated a significant improvement in participants’ understanding and ability to utilize AI technology effectively. Participants were able to create lesson plans, learning materials, quizzes, official letters, and educational content more efficiently using ChatGPT. Furthermore, the training enhanced participants’ awareness of ethical AI usage and digital literacy in educational environments. The program contributed positively to strengthening technological adaptation and supporting digital transformation in schools. Therefore, ChatGPT-based AI training can be considered an effective strategy to improve digital competencies and educational service quality in vocational schools.